PELAKSANAAN BEST PRACTICES DALAM PELAYANAN PAJAK KENDARAAN BERMOTOR RODA DUA OLEH BADAN PENDAPATAN PROVINSI RIAU (Studi Kasus Unit Pelaksana Teknis Pengelolaan Pendapatan Pekanbaru Kota) - Panggabean, Roriansah; Tua R.F.S, Harapan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Application of best practices in motorcycle tax service by Revenue Body of Pekanbaru at Technical Executor Unit was conducted by upgrading service quality, increasing people awareness (taxpayer), can raise service quality on the motorcycle taxpayer and also affected to determined target achievement of vehicle tax of Riau Province at Technical Executor Unit of Revenue Body Pekanbaru Kota. The research used qualitative descriptive method with research instruments referenced to Prasojo Theory (2004) and data collecting technique were interview, observation and documentary study that related to research purposes. The results indicated that application of best practices in motorcycle tax service by Technical Executor Unit, Revenue Management of Pekanbaru Kota was applied in order to increase service quality, such as the addition of working hours and service at day-off. However, yet to be optimal in reaching targets. Partnership is explored by controlling tax delinquents together with related institution. Beside that, complaint management that has not been available of tax payers become an obstruction to optimize of strategy continuity of service towards tax payers. Affected factors in applying best service on motor cycle tax service are lack of informational and technological personnel programmer in facing technological development, and lack of taxpayer awareness in paying motor cycle tax. Another factor was commutation of organisational main structure of Technical Executor Unit had been changed to Revenue Body in 2017.Keywords: Best Practices, Motorcycle Tax, Taxpayer.